(3QjGV GdfRgGJ aj TQM LGeY GdCegGJs - (3eMeO Hf YHO GdSdGe Hf jhSa Hf cKjQ GdghGQj GdefSJjQj, CHh YHO Gddg, GHf YHO GdSdGe , J (B749 (3g` s
(3ChdgG (B:s
(3GdMeO ddg Mb MeOg hSejJg H` CeG UGMH GdcJGH acfjJg HOQ GdOjf hLeGd GdOjf s
(3BNQgG (B:s
(3Ci dG jLhR ddeGdc Cf jMdH ef dHfgG EdG eG dG jVQ HfJGLgG dbhdg (B( (3U(B) (3dG VQQ hdG VQGQ s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3JHUQI GdYfhGf (B:s
(3TQM s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B205 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B171s
Keywords: (3Gdabg GdESdGejs